2019
DOI: 10.1103/physrevlett.122.153902
|View full text |Cite
|
Sign up to set email alerts
|

Sensing with Exceptional Surfaces in Order to Combine Sensitivity with Robustness

Abstract: Exceptional points (EPs) are singularities that arise in non-Hermitian physics. Current research efforts focus only on systems supporting isolated EPs characterized by increased sensitivity to external perturbations, which makes them potential candidates for building next generation optical sensors. On the downside, this feature is also the Achilles heel of these devices: they are very sensitive to fabrication errors and experimental uncertainties. To overcome this problem, we introduce a new design concept fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
136
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(137 citation statements)
references
References 59 publications
1
136
0
Order By: Relevance
“…In conclusion, we have investigated weak-force sensing in a squeezed cavity and theoretically showed that (i) the SQL cannot be surpassed in the case of G = 0 or θ = 0, (ii) the measurement precision of weak-force detection can be remarkably improved at the coupling strength smaller than g SQL by tuning the parametric phase and gain, and (iii) under the approximation of κ ω, quantum noise can be reduced without losing mechanical-mode information. Our work provides new insight in strengthening the sensitivity of a force sensor with the assistance of intracavity squeezing, which can be also extended into other systems of quantum sensing with e.g., waveguide [84,87], interferometer [88], or parity-time (PT ) symmetric microcavity [89][90][91]. In the future, we plan to extend our work to study the weakforce measurement with the help of two-mode squeezing or quantum entanglement [92][93][94], squeezed mechanical modes [70,95], or squeezed sources in hybrid COM devices [96,97].…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, we have investigated weak-force sensing in a squeezed cavity and theoretically showed that (i) the SQL cannot be surpassed in the case of G = 0 or θ = 0, (ii) the measurement precision of weak-force detection can be remarkably improved at the coupling strength smaller than g SQL by tuning the parametric phase and gain, and (iii) under the approximation of κ ω, quantum noise can be reduced without losing mechanical-mode information. Our work provides new insight in strengthening the sensitivity of a force sensor with the assistance of intracavity squeezing, which can be also extended into other systems of quantum sensing with e.g., waveguide [84,87], interferometer [88], or parity-time (PT ) symmetric microcavity [89][90][91]. In the future, we plan to extend our work to study the weakforce measurement with the help of two-mode squeezing or quantum entanglement [92][93][94], squeezed mechanical modes [70,95], or squeezed sources in hybrid COM devices [96,97].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, an EP sensor can also be excessively vulnerable to fabrication errors and imperfections that are inevitable in experiments. In this respect, exceptional surfaces have been suggested as a possible avenue to combine the robustness required for practical applications with the characteristic sensitivity offered by EPs [127]. One way to achieve this is to introduce a unidirectional coupling between the counterpropagating modes of a microring cavity.…”
Section: Enhancement Effects Around Epsmentioning
confidence: 99%
“…The types of non-Hermiticities and their manners of appearance are important for the non-Hermitian topological systems [34,54]. If the non-Hermiticity is = (0, 0, γ ), the topological phase transition and the existence of the edge state are unaltered because of the pseudo-anti-Hermiticity protection [34]; the topological properties of the non-Hermitian system are inherited by the EPs (exceptional rings or exceptional surfaces in 2D or 3D) [60][61][62][63][64][65][66][67]. If the non-Hermiticity is = (0, γ , 0), the non-Hermitian skin effect occurs under open boundary condition [54][55][56][57][58][59][68][69][70][71][72][73][74][75][76][77][78], the non-Hermitian Aharonov-Bohm effect under periodical boundary condition invalidates the conventional bulk-boundary correspondence [54], and the non-Bloch band theory is developed for topological characterization [77][78][79][80][81][82].…”
Section: Linking Topologymentioning
confidence: 99%